CULTURAL, MORPHOLOGICAL AND PHYSIOLOGICAL CHARACTERIZATION OF PHOMOPSIS VEXANS ISOLATES FROM DIFFERENT BRINJAL (SOLANUM MELONGENA L.) GROWING REGIONS OF KARNATAKA, INDIA - ROHINI; HG. GOWTHAM; P. HARIPRASAD; SR. NIRANJANA (International Journal of Pharma and Bio Sciences, 2016)
In the present study, an attempt was made to record the cultural, morphological and physiological characteristics of 23 isolates of Phomopsis vexans from different brinjal (Solanum melongena L.) growing regions of Karnataka, India. It was observed that all the isolates were varied considerably in the cultural characteristics such as mycelial type, colony colour, colony diameter, margin type and zonation when they were grown on five different media. All the media supported the pycnidia formation, but the isolate Pv7 was not found to produce pycnidia on all the tested media. The physiological tests indicated that all isolates showed maximum growth in the plates containing PDA medium at pH 5.6 and pH 6. Similarly, 27° C was found suitable for P. vexans growth and pycnidia formation. By analyzing the results, these isolates were broadly categorized into five groups which are not in accordance with their agro-climatic conditions.